High-Grade gliomas in pediatric patients after radiotherapy: A report of two cases at the Instituto Nacional de Ciencias Neurologicas – Lima, Peru. - Mego-Ramírez, Fiorela Noelí (2022)
Radiation therapy-induced high-degree gliomas (RIGs) are a rare complication with an ominous prognosis. Little is known about the underlying biology of RIGs, although some studies have suggested that there are no unique histologic or cytogenetic features to distinguish them from de novo glioblastomas. Two cases that meet the criteria to be considered RIG are reported, and pertinent pieces of literature are discussed. Two patients under 10 years of age, neither of whom had relevant genetic or clinical history, were diagnosed with primary cerebral gliomas at the National Institute of Neoplastic Diseases in Lima and, after radiation therapy cycles, developed high-degree secondary gliomas, confirmed in both patients by a histopathologic analysis. This report emphasizes the need to identify risk factors, molecular mechanisms of tumor development after radiotherapy, and probable therapeutic targets.